Environmental and Personal Factors Associated with Addiction Relapse in Referral patients to Marand Treatment Centers - Morteza Haghighi; Fariba Alizadeh; Tayebe Rezaei; Hamed RezakhaniMoghaddam; Habiballah Sodaei Zenoozagh; Asghar Mohammadpoorasl (Shahid Sadoughi University of Medical Sciences, 2018)
Introduction: The problem of relapse makes addiction treatment complicated because almost 80% of addicts relapse after treatment completion during the first six months. The purpose of this study was to determine the factors affecting relapse in addicts referred to addiction treatment centers in Marand. Methods: This study was a cross-sectional study that was performed on 306 patients in the city of Marand. The stratified sampling method was used. After collecting the questionnaire and determining its validity and reliability, questionnaires were distributed among an addicted group and as well as a non-addicted group. In the presence of the researcher, the patients answered the questions. Finally, the data were analyzed using statistical tests (chi-squared, independent t and ANOVA) applying SPSS software, version 21.0 for Windows. Results: In this study, the majority of participants in the addicted group and in the non-addicted group had a lower diploma and diploma respectively (90.2% and 90.8%). The mean age was the non-addicted group for 35.14 ± 8.23 years and in the non-addicted group and 32.72 ± 10.48 for the addicted group. According to the findings of this study, in the addicted group, the main reasons addiction relapse was family insistence (25.5% of cases). The non-addicted group mentioned the social conditions as the most common reason of success in the last quitting (22.9%). Based on the findings, a significant difference was found between the two variables including family size, employment status, smoking, family disputes, person's hopes and obsession to use drugs. Conclusion: For preventing and treating addiction, it is not enough to detoxify in treatment centers. It seems planning and interventions is necessary for preventing and reducing relapse, based on known major risk factors (such as employment status, smoking, family disputes, marriage, individual hope, and mental engagement with drug use).